Farm Animal Welfare—From the Farmers’ Perspective - Clive J. C. Phillips (Animals, 2024)
Improvements in the welfare of animals in the intensive production industries are increasingly being demanded by the public. Scientific methods of welfare improvement have been developed and are beginning to be used on farms, including those provided by precision livestock farming. The number of welfare challenges that animals are facing in the livestock production industries is growing rapidly, and farmers are a key component in attempts to improve welfare because their livelihood is at stake. The challenges include climate change, which not only exposes animals to heat stress but also potentially reduces forage and water availability for livestock production systems. Heat-stressed animals have reduced welfare, and it is important to farmers that they convert feed to products for human consumption less efficiently, their immune system is compromised, and both the quality of the products and the animals’ reproduction are adversely affected. Livestock farmers are also facing escalating feed and fertiliser costs, both of which may jeopardise feed availability for the animals. The availability of skilled labour to work in livestock industries is increasingly limited, with rural migration to cities and the succession of older farmers uncertain. In future, high-energy and protein feeds are unlikely to be available in large quantities when required for the expanding human population. It is expected that livestock farming will increasingly be confined to marginal land offering low-quality pasture, which will favour ruminant livestock, at the expense of pigs and poultry unable to readily digest coarse fibre in plants. Farmers also face disease challenges to their animals’ welfare, as the development of antibiotic resistance in microbes has heralded an era when we can no longer rely on antibiotics to control disease or improve the feed conversion efficiency of livestock. Farmers can use medicinal plants, pro-, pre- and synbiotics and good husbandry to help maintain a high standard of health in their animals. Loss of biodiversity in livestock breeds reduces the availability of less productive genotypes that survive better on nutrient-poor diets than animals selected for high productivity. Farmers have a range of options to help address these challenges, including changing to less intensive diets, diversification from livestock farming to other enterprises, such as cereal and pseudocereal crops, silvopastoral systems and using less highly selected breeds. These options may not always produce good animal welfare, but they will help to give farm animals a better life.